Back Cover: Bio‐Inspired Bimetallic Cooperativity Through a Hydrogen Bonding Spacer in CO2 Reduction (Angew. Chem. Int. Ed. 8/2023). Issue 8 (7th February 2023) - Zhang, Chanjuan; Gotico, Philipp; Guillot, Regis; Dragoe, Diana; Leibl, Winfried; Halime, Zakaria; Aukauloo, Ally
Abstract : Inspired by the active site of CO dehydrogenase, a metalloporphyrin‐based mimic has been synthesized combining a multipoint hydrogen bond donor and a bimetallic active centre, as reported by Zakaria Halime, Ally Aukauloo, and co‐workers in their Communication (e202214665) . The cooperativity between the two metal centres of the catalyst was shown for both homo‐ and heterobimetallic analogues, leading to a significant enhancement of the catalytic performance in the heterogeneous CO2 ‐to‐CO electrocatalytic reduction.